Factors affecting major choice of medical students in Azerbaijan - Abizada, Azar; Mirzaliyeva, Fizza (Technium Social Sciences Journal, 2023)
Studying the factors which influence the high school students’ major has become one of the frequent examined issues. This shows how important and interesting the findings are for different parties involved. To tackle the issue and find out the situation in Azerbaijan, around 700 first year students from 4 different programs studying the Azerbaijan Medical University were surveyed to get a look at how the decisions are made, by what and how much they are affected. A self-administered questionnaire was developed after carefully studying the already used questionnaires and factors for understanding the viewpoint of medical students in Azerbaijan. Factors like “wish to help society” and “job opportunities” were noticed to be very effective on the major choice of the students. “Parent’s suggestion” was following with its less but also considerable influence level.